Periodontopathic bacteria in rheumatoid arthritis pathogenesis: bridging clinical associations to molecular mechanisms - Guo, Xiaojing; Wang, Siwei; Ding, Jiuli; Liu, Weiwei; Xu, Jiaqi; Wang, Mutian; Sun, Hongyuan; Ma, Yuening; Liu, Wei; Zhang, Lei; Liu, Min (Frontiers in Immunology, 2025)
Periodontitis (PD) is a chronic inflammatory disease linked to microbial dysbiosis, while rheumatoid arthritis (RA) is an autoimmune disorder characterized by anti-citrullinated protein antibodies (ACPA). Despite their distinct etiologies, a clinical and serological association between PD and RA has been observed. Oral microorganisms, especially Porphyromonas gingivalis (P. gingivalis), may contribute to RA onset or progression through dissemination to joints or systemic inflammation. This review explores a: the role of oral microbiota and immune responses in RA b; clinical pathogenic pathways from oral pathogens to the joints c; mechanistic studies on the impact of periodontal pathogens on RA; and d. preventive and therapeutic strategies. P. gingivalis and other periodontal pathogens have been detected in synovial tissues and fluids of RA patients. Microbiome analyses show a more diverse oral microbiota with elevated periodontal disease-associated bacteria in RA patients. Studies demonstrate that P. gingivalis can induce citrullination, autoantibody production, and inflammation, exacerbating joint damage. Future research should investigate the impact of periodontal therapy and RA treatments on the oral microbiota, while large-scale clinical trials are needed to validate the causal relationship between periodontal pathogens and RA.